Impact of a Weekly Dance Class on the Functional Mobility and on the Quality of Life of Individuals with Parkinson’s Disease - Heiberger, Lisa; Maurer, Christoph; Amtage, Florian; Mendez-Balbuena, Ignacio; Schulte-Mönting, Jürgen; Hepp-Reymond, Marie-Claude; Kristeva, Rumyana (Frontiers in Aging Neuroscience, 2011)
Individuals with Parkinson´s disease (PD) mainly suffer from motor impairments which increase the risk of falls and lead to a decline of quality of life. Several studies investigated the long-term effect of dance for people with PD. The aims of the present study were to investigate (i) the short-term effects of dance (i.e. the effect immediately after the dance class) on motor control in individuals with PD and (ii) the long-term effects of 8 months of participation in the weekly dance class on the quality of life of the PD patients and their caregivers. The dance lessons took place in a ballet studio and were led by a professional dancer. Eleven people with moderate to severe PD (58-85 years old) were subjected to a motor and quality of life assessments. With respect to the motor assessments the Unified Parkinson Disease Rating Scale III (UPDRS III), the Timed up and go – Test (TUG) and the Semitandem – Test (SeTa) before and after the dance class were used. With respect to the quality of life and well-being we applied Quality of Life Scale (QOLS) as well as the Westheimer questionnaire. Additionally, we asked the caregivers to fill out the Questionnaire for caregivers. We found a significant beneficial short-term effect for the total score of the UPDRS motor score. The strongest improvements were in rigidity scores followed by significant improvements in hand movements, finger taps and facial expression. No significant changes were found for TUG and for SeTA. The results of the questionnaires showed positive effects of the dance class on social life, health, body-feeling and mobility, and on every day life competences of the PD patients. Beneficial effect was also found for the caregivers. The findings demonstrate that dance has beneficial effect on the functional mobility of individuals with PD. Further, dance improves the quality of life of the patients and their caregivers. Dance may lead to better therapeutic strategies as it is engaging and enjoyable.